The role of the habenula in the transition from reward to misery in substance use and mood disorders. (September 2017) - Batalla, Albert; Homberg, Judith R.; Lipina, Tatiana V.; Sescousse, Guillaume; Luijten, Maartje; Ivanova, Svetlana A.; Schellekens, Arnt F.A.; Loonen, Anton J.M.
Highlights: Habenula (Hb) plays a major role in reward and aversion. Lateral habenula (LHb) is involved in reward seeking. Medial habenula (MHb) is involved in misery-fleeing behavior. Enhanced LHb/MHb activity is implicated in the transition to addiction and depression. Abstract: The habenula (Hb) is an evolutionary well-conserved structure located in the epithalamus. The Hb receives inputs from the septum, basal ganglia, hypothalamus, anterior cingulate and medial prefrontal cortex, and projects to several midbrain centers, most importantly the inhibitory rostromedial tegmental nucleus (RMTg) and the excitatory interpeduncular nucleus (IPN), which regulate the activity of midbrain monoaminergic nuclei. The Hb is postulated to play a key role in reward and aversion processing across species, including humans, and to be implicated in the different stages of transition from recreational drug intake to addiction and co-morbid mood disorders. The Hb is divided into two anatomically and functionally distinct nuclei, the lateral (LHb) and the medial (MHb), which are primarily involved in reward-seeking (LHb) and misery-fleeing (MHb) behavior by controlling the RMTg and IPN, respectively. This review provides a neuroanatomical description of the Hb, discusses preclinical and human findings regarding its role in the development of addiction and co-morbid mood disorders, and addresses future directions in this area.